The consequences of the Russian-Ukrainian war on the Italian economy and the need for a ‘full and good employment’ strategy - Nicolò Giangrande (PSL Quarterly Review, 2023)
This article examines the consequences of the Russian-Ukrainian war on the Italian economy, especially on inflation, wages and employment. The study shows that Italy, which in the pre-war period had not yet reabsorbed all the consequences of the 2008 crisis, with the structural weaknesses of its economy, came under renewed pressure due to the COVID-19 crisis and, afterwards, to inflation and the war. The paper indicates the need for an economic policy based on the ‘full and good employment’ strategy.